Eye movement desensitization and reprocessing versus cognitive-behavioral therapy for adult posttraumatic stress disorder: systematic review and meta-analysis - Chen, Ling; Zhang, Guiqing; Hu, Min; Liang, Xia (The journal of nervous and mental disease, 2015)
Posttraumatic stress disorder (PTSD) is a relatively common mental disorder, with an estimated lifetime prevalence of ∼5.7%. Eye movement desensitization and reprocessing (EMDR) and cognitive-behavioral therapy (CBT) are the most often studied and most effective psychotherapies for PTSD. However, evidence is inadequate to conclude which treatment is superior. Therefore, we conducted a meta-analysis to confirm the effectiveness of EMDR compared to CBT for adult PTSD. We searched Medline, PubMed, Ebsco, Proquest, and Cochrane (1989-2013) to identify relevant randomized control trials comparing EMDR and CBT for PTSD. We included 11 studies (N = 424). Although all the studies had methodological limitations, meta-analyses for total PTSD scores revealed that EMDR was slightly superior to CBT. Cumulative meta-analysis confirmed this and a meta-analysis for subscale scores of PTSD symptoms indicated that EMDR was better for decreased intrusion and arousal severity compared to CBT. Avoidance was not significantly different between groups. EMDR may be more suitable than CBT for PTSD patients with prominent intrusion or arousal symptoms. However, the limited number and poor quality of the original studies included suggest caution when drawing final conclusions.